Dual-Band CP Metasurface-Array Antenna with Sequential-Phase Feed Network for C-Band Operation - Kakhong, Khwanlada; Phaebua, Kittisak; Phongcharoenpanich, Chuwong; Supreeyatitikul, Nathapat (My University, 2026)
This paper presents a four-cluster dual-band circularly polarized (CP) metasurface (MTS)-array antenna integrated with a sequential-phase feed (SPF) network for C-band applications. The antenna is implemented on dual-layer FR-4 substrates, incorporating both big- and small-sized MTS-array elements per cluster, with a tilted square-slot ground plane and microstrip-line feed. The SPF network excites each cluster with equal amplitude and 90° phase shifts, significantly enhancing return loss bandwidth (RLBW), axial ratio bandwidth, and realized gain. The simulated results demonstrate RLBW of 3.08 - 4.51 GHz and 4.94 - 8 GHz, and ARBWs of 3.08 - 4.66 GHz and 5.27 - 6.42 GHz for the lower and higher operating bands, respectively. The corresponding highest RHCP gains are 6.15 dBic at 3.8 GHz and 4 dBic at 6 GHz. The proposed antenna design achieves bi-directional radiation patterns and shows substantial performance improvements over conventional dual-band CP MTS-array antennas.
Keywords: Axial ratio bandwidth; circularly polarized antenna; metasurface; RHCP; sequential-phase feed network